Use of Internet As a Source of Information a Case Study of Medical Colleges In Delhi: Examining the use of the Internet as an information source in medical colleges in Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2012)
India has a long and distinguished tradition in science and technology fromthe ancient time. The great achievements during the year in medical science iscompared with developed countries. There is now a reservoir of expertise wellacquainted with latest technologies in medical science. At present there are264 medical colleges in the country out of which 185 medical colleges have beenrecognized by MCI and 90 new medical college have been permitted by the centralgovernment to conduct MBBS course.